THE ELEMENTS OF CULTURAL HERO MYTH IN W.B.YEATS' PLAYS ABOUT CUCHULAIN: THE UKRAINIAN CONTEXT - Hedzyk, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the plays “On Baile's Strand”, “The only jealousy of Emer”,”The Death of Cuchulain” by W.B. Yeats from the perspective unfolded at various levels of artistic structure of archetypical sense of cultural hero. Typologically similar images in Ukrainian drama limits XIX - XX centuries are traced and proved the dimension of analyzed mythologem for symbolist drama.